2019
DOI: 10.1155/2019/6352796
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Four‐Firm Competition Based on a Generalized Bounded Rationality and Different Mechanisms

Abstract: In this paper, the Caputo derivative with fractional orders is suggested to model a competition among four competing firms. The proposed economic model that describes this competition is constructed based on a generalization of the traditional bounded rationality. In this generalization, we study the influence of memory parameter on the complex behavior of the model. Memory means that we not only take into account the changes in quantities at a current time, but also study the changes occurring in the quantiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Another Cournot duopoly game with competed players having capacity constraints was considered based on utility function of Cobb-Douglas in Reference [9]. Other studies for Cobb-Douglas and the dynamic analysis for games based on it can be found elsewhere [10][11][12][13][14][15][16]. In Reference [17], the complex dynamic characteristics of a novel nonlinear finance system was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Another Cournot duopoly game with competed players having capacity constraints was considered based on utility function of Cobb-Douglas in Reference [9]. Other studies for Cobb-Douglas and the dynamic analysis for games based on it can be found elsewhere [10][11][12][13][14][15][16]. In Reference [17], the complex dynamic characteristics of a novel nonlinear finance system was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The Nash equilibria, their local stability and the presence of chaos are deeply investigated [17]. In [5] a discrete dynamic system that describes the competition among four firms is presented. In particular, the fractional bounded rationality is taken into account and the stability of the Nash point is studied [5].…”
mentioning
confidence: 99%
“…In [5] a discrete dynamic system that describes the competition among four firms is presented. In particular, the fractional bounded rationality is taken into account and the stability of the Nash point is studied [5]. However, while the fractional duopoly game, where two firms compete over a market, has been studied [19, 2, ?…”
mentioning
confidence: 99%
See 1 more Smart Citation